2007
DOI: 10.1196/annals.1401.013
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of the Medial Prefrontal Cortex, Orbitofrontal Cortex, and Dorsomedial Striatum to Behavioral Flexibility

Abstract: Behavioral flexibility refers to the ability to shift strategies or response patterns with a change in environmental contingencies. The frontal lobe and basal ganglia are two brain regions implicated in various components for successfully adapting to changed environmental contingencies. This paper discusses a series of experiments that investigate the contributions of the rat prelimbic area, infralimbic area, orbitofrontal cortex, and dorsomedial striatum to behavioral flexibility. Orbitofrontal cortex inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
350
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(386 citation statements)
references
References 48 publications
31
350
5
Order By: Relevance
“…Lesions of the dorsomedial striatum impair initial reversal learning, but not discrimination learning (Kirkby, 1969;Pisa and Cyr, 1990;Adams et al, 2001;Ragozzino et al, 2002;Palencia and Ragozzino, 2004;Featherstone and McDonald, 2005;Broadbent et al, 2007;Ragozzino, 2007). Based on these studies, we hypothesized that neurons in the dorsomedial striatum would show major changes in task-related activity (such as selective firing during Go or NoGo responding, as in the study by ) during reversal learning, but not during Go/NoGo learning.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Lesions of the dorsomedial striatum impair initial reversal learning, but not discrimination learning (Kirkby, 1969;Pisa and Cyr, 1990;Adams et al, 2001;Ragozzino et al, 2002;Palencia and Ragozzino, 2004;Featherstone and McDonald, 2005;Broadbent et al, 2007;Ragozzino, 2007). Based on these studies, we hypothesized that neurons in the dorsomedial striatum would show major changes in task-related activity (such as selective firing during Go or NoGo responding, as in the study by ) during reversal learning, but not during Go/NoGo learning.…”
Section: Introductionmentioning
confidence: 89%
“…Both of these cortical regions project to the dorsomedial striatum (McGeorge and Faull, 1989;Berendse et al, 1992;Cheatwood et al, 2003Cheatwood et al, , 2005. Moreover, differences in reversal behavior have been noted following lesions of the cortex and striatum (Dube et al, 1996;Ragozzino, 2007;Ragozzino and Rozman, 2007;Clarke et al, 2008), with cortical lesions having pronounced effects early in a reversal. These studies support the idea that orbitofrontal neurons represent the current value of a stimulus based on a comparison between expected and obtained outcomes (Schoenbaum et al, 2007).…”
mentioning
confidence: 99%
“…The present results suggest that dopaminergic modulation of reversal learning likely occurs through actions on D 2 receptors located in regions other than the NAc. In this regard, although the OFC is critical in facilitating reversal shifts (Dias et al, 1996;McAlonan and Brown, 2003;Ragozzino, 2007;Ghods-Sharifi et al, 2008), mesocortical DA depletion does not affect this form of flexibility (Crofts et al, 2001). The possibility remains that the certain subregions of the dorsal striatum may be the critical locus where D 2 receptors enable shifts between different stimulus-reward contingencies, although striatal DA depletion has yielded inconsistent effects on reversal learning (Collins et al, 2000;Crofts et al, 2001;O'Neill and Brown, 2007).…”
Section: A Selective Role For Nac D 1 Receptors In Strategy Set-shiftingmentioning
confidence: 99%
“…Later studies revealed that mPFC lesions can also cause no impairment in spatial navigation, but rather result in a deficit of behavioural flexibility (De Bruin et al 1994, 2001Lacroix et al 2002). In various tests, it has been shown that destruction or inactivation of mPFC does not affect learning and memory per se, but impairs the animals' ability to shift strategy, or rule out inappropriate strategies when task demands are changed or environmental conditions are altered (Ragozzino et al 1999a, b;Delatour and Gisquet-Verrier 2000;Dias and Aggleton 2000;Lacroix et al 2002;Sullivan and Gratton 2002;Passetti et al 2002;Ragozzino et al 2003;Ragozzino 2007). At first sight, in relation to RE-mPFC connectivity, these reports seem contradictory to the rapid strategy shifting by RE-rats.…”
Section: Effects Of Hippocampal Versus Thalamic Lesionsmentioning
confidence: 99%